Monocyte Chemotactic Protein 1-Induced Protein 1 Is Highly Expressed in Inflammatory Bowel Disease and Negatively Regulates Neutrophil Activities - Jian Lin; Gengfeng Li; Chunjin Xu; Huiying Lu; Cui Zhang; Zhi Pang; Zhanju Liu (Mediators of Inflammation)
Monocyte chemotactic protein 1-induced protein 1 (MCPIP-1) is highly expressed in activated immune cells and plays an important role in negatively regulating immune responses. However, its role in regulating neutrophil functions in the pathogenesis of inflammatory bowel disease (IBD) is still unclear. Here, we found that MCPIP-1 was markedly increased at both the transcriptional and translational levels in inflamed mucosa of IBD patients compared with healthy controls, which was mainly expressed in neutrophils. Interestingly, MG-132, a proteasome inhibitor reducing the degradation of MCPIP-1, further facilitated neutrophils to express MCPIP-1 in vitro. Importantly, MCPIP-1 markedly downregulated the production of ROS, MPO, and proinflammatory cytokines (e.g., interleukin-1β, interleukin-6, tumor necrosis factor-α, interleukin-8, and interferon-γ) and suppressed the migration of IBD neutrophils. Consistently, the same functional changes were observed in neutrophils from mice with myeloid-targeted overexpression of MCPIP-1 as MG-132 did. Altogether, these findings suggest that MCPIP-1 plays a negative role in regulating neutrophil activities through suppressing the production of ROS, MPO, and proinflammatory cytokines and inhibiting the migration. MG-132 may partially modulate the function of neutrophils via the induction of MCPIP-1. Therefore, targeting MCPIP-1 or exogenous supplementation of MG-132 may provide a therapeutic approach in the treatment of IBD.